Critical growth and energy barriers of atomic-scale plastic flow units in metallic glasses. (September 2021) - Yu, J.H.; Shen, L.Q.; Şopu, D.; Sun, B.A.; Wang, W.H.
Graphical abstract: Abstract: We provide an intuitive interpretation for critical growth of an atomic-scale plastic flow unit in metallic glasses through energy conversion approach. An explicit expressions for the critical stress upon which the plastic flow unit can grow spontaneously is obtained. The growth of the atomic units is an competition process between the intrinsic configurational entropy change and the constraint effect of glassy matrix on the inelastic deformation of plastic flow unit. Our analysis shows that at the yielding point, the activation of a plastic flow unit should take the easiest path in the potential energy landscape. In this case, the change of the intrinsic configurational entropy and the elastic constraint effect contribute equally to the activation energy barrier for the plastic flow unit. Our results provide quantificational insights on the microscopic origin of the plastic yielding of glassy solids.